Parentalidade compartilhada: revendo o legado intergeracional - Spinelli, Maria Eliza Buzetti (2006)
ABSTRACT This study focuses on parenting, which herein is defined as shared parenting, whereby both the father and the mother share child caring and are providers. The study observed indications provided by family history of parents who facilitate this type of parenting. Four couples in a stable relationship and living in a double-income household, with ages ranging from 30 to 45, where family income is fifteen to forty minimum salaries and that have one or more children from three to seven years old were interviewed together, using a semi-structured questionnaire based of the genogram s construction. The analysis of colleted material was conducive to the conclusion that familial customs are a strong influence on the constitution of parents who share parenting. Whether by repeating role-models or to learn how to do things differently, father and mother roles and the style of the marriage itself are the basis of shared parenting. The approval of novel mother and father role-models by their own parents seems to be a facilitating element for change, as well as the existence of individuals from preceding generations who showed affection and who are admired by the interviewees parents. The influence of culture and of values of a closely-knit family, and the sound sense of individuality that interviewees were able to establish with their families seem to be determining factors for shared parenting. This study is concluded with the assurance that parenting is undergoing changes at this moment; sharing is still disproportionate, where men and women are overburdened with different aspects; however, due to the recognition given to our interviewees by their families, it seems that an equal relationship is increasingly more desired in relationships